Performance of Rabi Crops in Relation to Stored Soil Moisture at Sowing - Mallappa, M; Radder, G D (Annals of Arid Zone, 2016)
Investigation on response of different rabi crops to the stored soil moisture level (125, 200 and 275 mm) at sowing revealed that sorghum, sunflower, wheat and gram could extract the soil moisture only from 0 to 60 cm soil depth and only sunflower could extract the soil moisture from 60 to 100 cm soil depth. At low soil moisture level (125 mm), sorghum utilized the highest soil moisture. While, at high soil moisture level (275 mm) safflower utilized more moisture and recorded the highest per cent increase in total drymatter and grain yield. However, irrespective of soil moisture level, sorghum recorded the highest grain yield, water use efficiency, crop equivalent yield and net income. Results lead to the conclusion that rabi sorghum at low soil moisture level (125 mm) and safflower and sunflower at medium (200 mm) and higher (275 mm) stored soil moisture levels gave higher grain yield and net income.